Exploring the perception of different stakeholders regarding BRAC pre-primary schools - Aker, Shaheen (BRAC Research and Evaluation Division (RED), 2019)
BRAC began piloting its pre-primary school program with 40 schools in 1997. The number of ongoing pre-primary schools stands at 950 at present. Another 484 schools have already been closed. The present study is based on these pre-primary schools focusing on different stakeholders' perceptions ont the schools. The study was conducted in four schools from two BEP (BRAC Education Progranune) regions of Jarnalpur and Rangpur. Data were collected from parents, teachers. committee members, community people, BRAC staff. and learners. Data collection was done by focused group discussions, informal discussions, classroom observations, semi-structured interviews and a mini achievement test using checklists and a test instrument. Title findings revealed that almost all the respondents expressed a positive view· on the preprimary education. There were no significant differences between the behaviour and the performance of ex-preprimary learners and those of formal primary learners. About 50% of the learners were found to be admitted into the formal schools after completing the preprimary education. However, around half of them could not continue their schooling regularly or dropped out of the formal schools after a few months. The study suggests that the preprimary school should be established within the catchment area of formal primary schools and provisions should be made for a follow up by BRAC staff regarding preprimary learners' admission into the formal primary schools. The study also suggests that teachers' salary should be increased where a further study would provide more in-depth information on the programme.